Community banks versus non‐community banks: Post the Great Recession. (13th November 2021) - Fayman, Alex; Chen, Su‐Jane; Mayes, Timothy
Abstract: Community banks (CBs), despite holding a fairly small share of US banking assets, provide vital financial services to key segments of the economy and fill a void untapped by larger non‐community banks (Non‐CBs). They face challenges brought on by a fast‐changing banking landscape, evolving technology, and ever‐increasing regulatory burden. To remain competitive and to gain scale‐related efficiencies, CBs have been seeking mergers even as greater institutional size causes a departure from the classical relationship‐based business model. This study examines performance of US CBs and Non‐CBs post the Great Recession to reveal how size of these institutions may affect their business operations. Empirical findings show that CBs, compared with their larger counterparts, tend to maintain higher levels of liquidity and lower levels of capital, and demonstrate a greater dependence on core deposits, confirming that CBs focus on deposit taking and soft information‐based lending strategies. Furthermore, this study suggests that CBs should not be considered a homogenous group operating under a singular business model and cautions that regulatory dialectics aimed at the banking industry should not employ a one‐size‐fits‐all approach.